Answer :

Answer:  1

=================================================

Explanation:

The rule is

x^0 = 1

where x is nonzero (ie, not equal to zero). So whatever number you raise to the zeroth power, the answer is always 1.

---------------

Let's see why this rule works

x^1 = x   ... raising something to the first power is itself

(x^1)/x = x/x ... divide both sides by x

(x^1)/x = 1 .... turn the 'x/x' into 1

(x^1)/(x^1) = 1 .... rewrite the second 'x' as 'x^1'

x^(1-1) = 1 ... subtract exponents

x^0 = 1

Answer:

um

Step-by-step explanation:

Other Questions